2012
DOI: 10.3748/wjg.v18.i40.5729
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscularvsintradermal route for hepatitis B booster vaccine in celiac children

Abstract: Our study suggests that both ID and IM routes are effective and safe options to administer a booster dose of HBV vaccine in celiac patients. However the ID route seems to achieve a greater number of high responders and to have a better cost/benefit ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 34 publications
0
43
0
2
Order By: Relevance
“…Clinical trials with various other viral vaccines administered i.d. yielded promising data (11,12,21). However, poor immune responses have also been reported after i.d.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical trials with various other viral vaccines administered i.d. yielded promising data (11,12,21). However, poor immune responses have also been reported after i.d.…”
Section: Discussionmentioning
confidence: 94%
“…Four weeks after every booster dose, 90% of ID patients and 96.4% of IM subjects showed a protective anti-HBs titer after a third booster dose. The authors concluded that both routes are efective in revaccinating CD patients; however, the ID route seems to produce a signiicantly higher percentage of higher responders [47].…”
Section: New Approaches In Hepatitis B Vaccination In Celiac Childrenmentioning
confidence: 99%
“…Data suggest that the ID route ofers greater immunogenicity due to direct delivery of antigen to the skin immune system, using even lower doses of antigen than IM route [47]. Moreover, the presence of a skin reaction on the site of the intradermal injection could represent a less expensive strategy to test serum anti-HBs response after the booster dose [48].…”
Section: New Approaches In Hepatitis B Vaccination In Celiac Childrenmentioning
confidence: 99%
“…While this level is achieved in 85-100 % of the general population, titers reach acceptable levels in only 64 % of dialysis patients (Chaves et al 2011), 41-60 % of individuals positive for HIV (Landrum et al 2012;Laurence 2005), 35 % of individuals with irritable bowel disease (Vida Pérez et al 2009), 50 % of celiac disease patients (Ahishali et al 2008;Leonardi et al 2009), 38 % of obese individuals (Roome et al 1993), 30-58 % of the elderly (Roome et al 1993;Tohme et al 2011;Williams et al 2012), and 57 % of those with chronic kidney disease (Zitt et al 2011). There is some evidence that other routes of vaccine administration may be effective in eliciting responses in nonresponders, such as by intradermal administration in healthcare workers (Levitz et al 1995;Nagafuchi et al 1991;Roukens et al 2010) and in children with celiac disease (Leonardi et al 2012). Unfortunately the present commercial vaccines are not approved for intradermal administration and further resources will need to be allocated to pursue this healthcare model.…”
Section: Hepatitis B Epidemiologymentioning
confidence: 99%